Factors associated with daily cigarette smoking among 60-65 aged adults: a cross-sectional study. (Colombia Medica, 2007)
Background: Cigarette smoking decreases gradually with aging. However, an important number of people older than 60 years continue smoking. Objective: To know the prevalence and associated factors with daily cigarette smoking among adults aged between 60- and 65-years old from the general population of Bucaramanga, Colombia. Method: A cross-sectional study was carried out among 60- and -65 years old adults. Sociodemographic characteristics, medical condition, coffee intake, abusive alcohol consumption, common mental disorders, personality features (DSM-IV), and daily cigarette smoking within the last month were evaluated. Confounding factors were controlled with non-conditional logistical regression. Results: A group of 208 people were interviewed. The mean age was 62.9 years (SD, 2.0); the mean education was 6.1 years (SD, 3.7); 67.3% of them were women; 68.3% were married; 45.2% had an employ; 77.4% lived in middle class neighborhood; 40.9% suffered from a medical condition; 40.9% drunk coffee within the last month; and 12% reported a common mental disorder. A ratio of 30.8% reported cluster A personality features; 37.5%, cluster B; and 53.8%, cluster C. The prevalence of daily cigarette smoking was 6.3% (95% CI 3.0-9.6), and it was associated with daily coffee drinking (OR 13.9); after controlling for sex and abusive alcohol consumption. Conclusions: Cigarette smoking is present in one out of sixteen people aged 60-65 years-old, and it is related to other risk-health behaviors.